Regional Applications of Drone Data Processing Technology in Vietnamese Coffee Plantations - Pham M. Tuan (Innovation in Science and Technology, 2025)
Vietnam, the world’s second-largest coffee producer, faces challenges such as inconsistent quality, inefficient farming, and climate change. Drone data processing technology offers transformative solutions, especially in the Central Highlands, by providing high-resolution data on crop health, soil conditions, pests, and irrigation. Key applications, including precision agriculture, targeted irrigation, and yield estimation, enhance productivity, reduce waste, and promote sustainability. Drone adoption fosters rural economic growth and positions Vietnam as a leader in sustainable coffee production. This paper examines the role of drones in revolutionizing Vietnamese coffee farming while addressing environmental and economic challenges.